Pengaruh Cholecalciferol 1000 IU pada Kekuatan Genggam Tangan Lansia dengan Defisiensi Vitamin D: The Effects of Cholecalciferol 1000 IU Supplementation on Handgrip Strength in Elderly with Vitamin D Deficiency - Ika Swasti Mahargyani; Enny Probosari; Aryu Candra; Hertanto Wahyu Subagio; Khairuddin Khairuddin (Universitas Airlangga, 2023)
Backgrounds: Vitamin D regulates muscle function by binding to vitamin D receptors (VDR) via genomic signaling pathways. The biologically active form of vitamin D (1,25-(OH)D) affects muscles by modulation of gene transcription and protein kinase signaling pathways that support proliferation and muscle growth. Aging will result in the interaction of vitamin D and VDR, affecting the regulation of muscle calcium channels, followed by a decrease in the stimulation of muscle contractions. Decreased synthesis and low vitamin D intake also affect serum level 25(OH)D. Maintaining vitamin D status in the elderly with vitamin D deficiency is expected to inhibit the decline in muscle strength and dysfunction. Objectives: Determining the effect of giving cholecalciferol on handgrip strength. Methods: An experimental study with randomized controlled trial (RCT) enrolled 54 elderly divided into treatment and control groups. The treatment group received cholecalciferol 1000 IU/day, and the control group received a placebo for 12 weeks. Both groups were examined for serum 25(OH) levels before and after treatment. Results: Most samples in both groups (79.62%) showed vitamin D deficiency. There was an effect of 1000 IU cholecalciferol supplementation on serum 25(OH)D levels with a mean change of 3.8 (p<0.001), while the grip strength showed insignificant results with a mean change of 0.5 (p=0.748). No significant relationship existed between serum 25(OH)D level changes and hand grip strength (r=0.02; p=0.87). Conclusions: Cholecalciferol supplementation of 1000 IU/day for 12 weeks increased serum vitamin D levels but did not increase grip strength.